Analysis of the Performance of the Fish School Search Algorithm Running in Graphic Processing Units - Lins, Anthony J. C. C.; Bastos-Filho, Carmelo J. A.; Nascimento, Débora N. O.; Junior, Marcos A. C. Oliveira; Lima-Neto, Fernando B. de (IntechOpen, 2012)
None